Pengajaran Semantik pada Mahasiswa IKIP PGRI Pontianak - Simarmata, Mai Yuliastri (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2020)
This study aims to determine the process of semantic teaching in IKIP PGRI Pontianak students. The technique used in this research is direct observation and direct communication techniques. While the tools used are obesservation guidelines and interview guidelines. The processing and analyzing of the data is carried out through reflection activities. Data collected through essay test related to synonymy and antonym. The data analysis technique was carried out in stages (1) checking the result of observation carefully (2) determing the suitability of the formulation of learning objectives made by lecturers in teaching listening subject related to meaning relations (3) determing theÂ  suitability of the material with the learning objective 94) analyzing the suitability of learning activities conducted by the lecturer (5) Analysis of interview data by the lecture (6) The results of IKIP PGRI Pontianak student research in general can distinguish the relation of meaning related to synonymy and antonym.